Multivariate analysis in the evaluation of soil attributes in areas under different uses in the region of humaitá, AM - Pantoja, José Carlos Marques; Campos, Milton César Costa; Lima, Alan Ferreira Leite De; Cunha, José Maurício Da; Simões, Emily Lira; Oliveira, Ivanildo Amorim De; Silva, Laércio Santos [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2019)
The recognition of the influence of management practices on soil physical and chemical conditions is substantial for sustainable agriculture. For this reason, this study was developed for the purpose of evaluating the behavior of soil attributes under different uses in the region of Humaitá, AM, using multivariate statistical methods. The study was developed in 8 rural properties producing bananas, grassland, maize, coffee, cassava, vegetables, agroforestry system and a forest fragment. Samples of soils with preserved structure in the 0.0 - 0.10 and 0.10 - 0.20 m layers were randomly collected in 5 small trenches per area, totaling 32 samples in the management systems, to determine the physical and chemical attributes. The data were then submitted to univariate and multivariate statistical analysis. Exploratory data analysis (principal components and dendrogram) and frequency of environmental covariates was efficient in distinguishing production environments, so multivariate classification based on physical and chemical attributes of the soil can help in the proper planning of land use. The analysis of the principal components indicates that the BD presents direct dependence with the SPR, signaling the use of the soil with grassland the only one in the process of compaction. Soil acidity is the main limiting factor for crop development, requiring the adoption of pH corrective practices with improvements in nutrient supply. The conversion of the forest to grassland maintained the structural characteristics of the soil, while the other uses increased improvements in physical quality and soil fertility.
Análise multivariada na avaliação de atributos do solo em áreas sob diferentes usos na região de humaitá, AM
Keywords: Environmental covariates; Physical and chemical attributes; Soil management